(untitled) (Research, Society and Development, 2023)
Introduction: The increasing popularity of motorcycles as a means of transportation has been accompanied by a concerning rise in the number of accidents and traffic-related deaths. Objective: This study aimed to assess the epidemiological profile of motorcycle riders involved in traffic accidents and treated in the State of Pará, during the period from 2010 to 2020. Method: This study utilized a descriptive and quantitative ecological epidemiological design to evaluate hospital morbidity in the State of Pará from 2010 to 2020. Hospital morbidity information was obtained from DATASUS using TABNET, and population data from IBGE. Result: Over 100,000 hospitalizations were recorded in the State of Pará, with the majority occurring in Metropolitan Region I, where the Municipality of Ananindeua is located. This municipality not only led in the number of hospitalizations but also topped the list of municipalities with the highest number of deaths. The prevalence was higher among males, individuals of mixed race, and those aged between 20-24 years. The mortality rate was highest in the Municipality of Belém, with an average stay of 11.3 days. Conclusion: The Municipalities of Ananindeua and Belém emerge as epicenters of this scenario, thus emphasizing the need for preventive actions and traffic safety policies in these two locations.